A Scalable Synthesis of Chiral Modular Phosphine–Phosphite Ligands - Dindaroğlu, Mehmet; Falk, Anna; Schmalz, Hans-Günther (Synthesis, 2013)
The outstanding usefulness of phenol-derived chiral phosphine–phosphite ligands has recently been shown in a number of transition-metal-catalyzed C–C bond-forming reactions. This is exemplified by the synthesis of five new ligands in an optimized procedure that can be reliably performed on a multigram scale.
Keywords: Chiral P,P-ligands; enantioselective catalysis; bromine–lithium exchange; synthetic methods; asymmetric 1,4-addition